Fishers’ perception on co-operative services and willingness-to-pay (WTP) for improved fish marketing services at Njarakkal, Ernakulam District, Kerala - Jeyanthi, P.; Chandrasekar, V.; Gopal, Nikita (Indian Journal of Fisheries, 2018)
Fishermen co-operatives play a vital role in providing services which are uniform in nature. But, the perception of fishermen regarding co-operative services is generally subjective. This study assessed the fishermens’ perception at Njarakkal, Ernakulam District, Kerala, regarding the services of co-operatives. It was found from the results that 90% of respondents strongly agreed that they were earning profit by selling fish through co-operatives. More than 80% accepted that co-operatives were the best credit source, binding the fishermen and improving standard of living. About 50% felt that co-operatives had no role in fisheries management. Besides provision of credit, fish auctioning is an important service rendered by fishermen co-operatives. It has been felt that there is lack of proper infrastructure facilities, especially cold storage facility in the domestic fish marketing system. The willingness-to-pay for improved marketing services at Njarakkal, was also evaluated during this study. The willingness-to-pay for setting up cold storage facility was assessed using logistic model. Results revealed that 65% of respondents are willing-to-pay for the cold storage facility. The results of logistic regression analysis showed that member’s satisfaction regarding co-operative activities is the most significant factor which decides their willingness-to-pay for the improved marketing services.